From Microbiome to Inflammation: The Key Drivers of Cervical Cancer - Zhou, Zi-Wei; Long, Hui-Zhi; Cheng, Yan; Luo, Hong-Yu; Wen, Dan-Dan; Gao, Li-Chen (Frontiers in Microbiology, 2021)
Cervical cancer is the third leading cause of cancer-related death worldwide. Microbes and hosts form a mutually beneficial symbiosis relationship, and various parts of the host body are microbial habitats. Microbes can trigger inflammation in certain parts of the host body, contributing to cervical cancer development. This article reviews the relationship between cervicovaginal microbes, inflammation and cervical cancer, and discusses the effect of some key cervical microbes on cervical cancer. Finally, probiotic therapy and immunotherapy are summarized.